1980
DOI: 10.1111/j.1432-1033.1980.tb04838.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a Functional Acetylcholine Receptor

Abstract: The 'reconstitution cycle' is composed of the following sequence of operations. Highly purified receptor-rich membranes prepared from Torpedo marmorata electric organ are exposed to pH 11 to remove the 43000-M, protein and dispersed into solution by sodium cholate under conditions where more than 8 5 % of the receptor protein is in its 9-S form. Elimination of the detergent by filtration on a Sephadex column (or dialysis) yields a 'reconstituted receptor' fraction, under conditions which conserve part of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 69 publications
(60 reference statements)
5
38
0
Order By: Relevance
“…Spectroscopic (12) and photolabeling experiments (14) suggested that the Mr 43,000 protein bound local anesthetics, raising the possibility that it might be part of the AcCho-activated cation channel. However, Neubig et aL (9) demonstrated, and others have confirmed (10,15,16), that the Mr 43,000 protein can be removed from the membranes by treatment at pH 11 without altering either the binding of cholinergic ligands or the control of ion permeability.…”
mentioning
confidence: 99%
“…Spectroscopic (12) and photolabeling experiments (14) suggested that the Mr 43,000 protein bound local anesthetics, raising the possibility that it might be part of the AcCho-activated cation channel. However, Neubig et aL (9) demonstrated, and others have confirmed (10,15,16), that the Mr 43,000 protein can be removed from the membranes by treatment at pH 11 without altering either the binding of cholinergic ligands or the control of ion permeability.…”
mentioning
confidence: 99%
“…It might account for the heterogeneity of binding reported for [3H] trimethisoquin with ACh-receptor-rich membrane fragments, and for the differential effects of HTX on this binding [15]. It could also explain the results obtained upon covalent labelling by UV irradiation of the polypeptide chains of the ACh-receptor protein with radioactive noncompetitive blockers [34].…”
Section: Discussionmentioning
confidence: 99%
“…They include, among others, the aminated local anesthetics proadifen and dimethisoquin [3][4][5][6][7], the frog toxin histrionicotoxin (HTX) and its derivatives [8][9][10][11], the hallucinogenic drug phencyclidine [12][13][14]. These pharmacological agents block the physiological response in the/~M range and their binding to saturable sites on ACh-receptor-rich membrane fragments isolated from Torpedo electric organ has been demonstrated with the radiolabelled derivatives [3H]meproadifen [6], [3H] trimethisoquin [ 15 ], [all] perhydro-HTX [ 11,[16][17][18] and [3H]phencyclidine [12,19,20]. A number of structurally unrelated compounds usually considered as primarily interacting with the lipid phase of the membrane, such as the detergents Triton X-100 or Na-cholate [21,22], fatty acids [21,36], phospholipases (reviews [23,27]), general anesthetics and alcohols [7,24[ also block the response to ACh in a noncompetitive manner.…”
Section: Introductionmentioning
confidence: 99%
“…Solubilization of membranes with cholate was performed according to Sobel et al (1980). To 1 volume ofmembranes at 2.5 mg proteinlml in 0.1 M %is, pH 6.8, was added 1/9 volume ofcholate 31%.…”
Section: Methodsmentioning
confidence: 99%